Mathematical modeling of particle deposition and distribution in indoor environments - Chen, Fangzhi (2008)
Indoor air quality is now receiving more attention than ever before and it is known that indoor particulate matters have significant influences on indoor air quality. A few numerical models have been developed to study indoor particle dynamics by either the Lagrangian or the Eulerian approach. However, some of the important features of indoor particles, for example, the effect of turbulent dispersion for the Lagrangian simulations and the modeling of deposition for the Eulerian models, were overlooked or modeled improperly and we still do not have an effective prediction tool which is able to model both spatial and temporal profiles of indoor particle distribution and deposition quantitatively. The primary objective of the present work is to study particle deposition and distribution in indoor environments by means of both Lagrangian simulation and Eulerian modeling and to gain more understanding of the behavior of indoor particles with different sizes.